2016
DOI: 10.1021/acs.jpca.5b10450
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study of the Role of Interface Curvature on Multicomponent Vapor–Liquid Phase Equilibrium

Abstract: The effect of interface curvature on phase equilibrium has been much more studied for single-component than multicomponent systems. We isolate the effect of curvature on multicomponent vapor-liquid equilibrium (VLE) phase envelopes and phase composition diagrams using the ideal system methanol/ethanol and the nonideal system ethanol/water as illustrative examples. An important finding is how nanoscale interface curvature shifts the azeotrope (equal volatility point) of nonideal systems. Understanding of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…In order to gain insight into the potential mechanism which fixes this hole size R H , let us consider the different pressures acting in the bubble layer during the drying process − as sketched for the cross‐section of one bubble in Figure b. Let us associate a pressure drop Δ P between the liquid pressure P L and the ambient pressure P 0 , leading to a mean curvature C of the air/liquid interface between the bubbles ΔP=P0PnormalL=γC where γ is the surface tension . Since we can consider γ as constant everywhere, the bubble cap has the form of a section of a sphere whose radius of curvature R is related to the bubble pressure P B and the atmospheric pressure via the Laplace law PnormalBP0=4γR. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain insight into the potential mechanism which fixes this hole size R H , let us consider the different pressures acting in the bubble layer during the drying process − as sketched for the cross‐section of one bubble in Figure b. Let us associate a pressure drop Δ P between the liquid pressure P L and the ambient pressure P 0 , leading to a mean curvature C of the air/liquid interface between the bubbles ΔP=P0PnormalL=γC where γ is the surface tension . Since we can consider γ as constant everywhere, the bubble cap has the form of a section of a sphere whose radius of curvature R is related to the bubble pressure P B and the atmospheric pressure via the Laplace law PnormalBP0=4γR. …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it raises one important question: which physical mechanism could fix a characteristic, bubble‐size‐independent pressure drop Δ P of the order of 2 000 Pa between the liquid and the surrounding air at the final drying stage? One possibility could be that the rather monodisperse latex size leads to a characteristic dimension of the liquid meniscus between the latex particles at the final drying stage whose curvatures could be sufficiently strong to influence the vapor pressure . Another possibility may be that the disjoining pressure in the thin film (which is typically of the order of a few thousand Pa) plays a role in fixing the pressure relations.…”
Section: Resultsmentioning
confidence: 99%
“…used one rigorous EOS model and capillary pressure equation to calculate the phase envelope of multicomponent mixtures, and concluded that small pore sizes result in great change in the phase envelope. Shardt and Elliott analyzed the effect of interface curvature on multicomponent vapor–liquid equilibrium phase envelopes and phase compositions diagrams. Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Sandoval et al 29 used one rigorous EOS model and capillary pressure equation to calculate the phase envelope of multicomponent mixtures, and concluded that small pore sizes result in great change in the phase envelope. Shardt and Elliott 30 analyzed the effect of interface curvature on multicomponent vapor-liquid equilibrium phase envelopes and phase compositions diagrams. Zhang et al 25 studied the effect of capillary pressure on the phase behavior of CO 2 /hydrocarbons in unconventional reservoirs, and the results indicated that reduction in the nano pore size causes a noticeable difference in the two-phase envelope.…”
Section: Introductionmentioning
confidence: 99%
“…A relatively small number of papers have been devoted to nanoscale phase equilibria of two-component systems [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. For binary and multi-component solutions, the configurational entropy is one of the basic terms of the Gibbs energy of the solution phases, and thus its precise knowledge is crucial for nano-equilibrium calculations.…”
Section: Introductionmentioning
confidence: 99%